Business analytics as a driver of organizational performance: Evidence from the pharmaceutical industry - Soliman, Karim; Nazneen, Afroze; Ambreen, Adina; Haque, Rasheedul; Jeet, Vikramjeet (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of business analytics in enhancing organizational performance within the pharmaceutical industry. Business analytics, encompassing data collection, analytical tools, technology, human resources, strategic alignment, performance measurement, and compliance, is crucial for driving informed decision-making and strategic planning. A quantitative approach was employed, surveying 162 professionals across various managerial levels in pharmaceutical companies. A structured questionnaire assessed the impact of business analytics on organizational performance, focusing on financial, operational, market, employee, and sustainability metrics. Data were analyzed using SPSS software, with reliability, descriptive, and regression analyses conducted to evaluate the relationship between business analytics and performance outcomes. The results revealed a high Cronbach’s Alpha value (0.980), indicating excellent reliability. Descriptive statistics showed moderate agreement with business analytics practices, while regression analysis demonstrated a strong positive correlation (R = 0.762) between business analytics and organizational performance, explaining 58% of the variance. The findings underscore the critical role of business analytics in improving financial performance, operational efficiency, market share, employee productivity, and sustainability within the pharmaceutical industry. Organizations are encouraged to invest in advanced analytics tools and technologies to drive strategic alignment and enhance overall performance.